Tren Konsumsi Mie Samyang di Kalangan Mahasiswa: Pertimbangan Labelisasi Halal dan Promosi Produk Pada Keputusan Membeli - Yustiani, Sofia; Ernawati, Ernawati (Mabsya: Jurnal Manajemen Bisnis Syariah, 2022)
Purchasing decisions are the actions of consumers to be willing to buy or not against a product. Many factors can influence a consumer's purchasing decision on a product. Therefore, entrepreneurs are required to understand the behavior of consumers in purchasing, especially in Indonesia whose people are the majority of Muslim consumers, one of which is by halal labeling and promotion. The review means to examine the impact of halal naming and advancement on the buying choices of Samyang noodel. This study utilizes quantitative examination strategies. The populace in this study was understudies at UIN Prof. KH. Saifuddin Zuhri Purwokerto. The testing strategy utilized is non-likelihood inspecting with purposive examining procedure utilizing 100 essential information acquired from polls. Information examination is done through spearman rank connection, composed concordance of kendal w and ordinal relapse investigation utilizing SPSS. The results of the study using spearman rank correlation analysis can be concluded that halal labelization and partial promotion have a positive and significant effect on purchasing decisions. With the results of the correlation coefficient of halal labelization variables with purchase decisions of 0.838 and coefficients of correlation of promotional variables with purchasing decisions of 0.848. While the correlation of kendal w concordance of 0.430 showed a simultaneous relationship between halal labeling and promotion of purchase decisions in a positive direction, while ordinal regression testing on the Fitting Information model table showed that both independent variables of halal labeling and promotion significantly affected the decision to purchase Samyang noodle in students at UIN Prof. KH. Saifuddin Zuhri Purwokerto.